Multiliteracy of Primary School Science Based on Local Wisdom in the Era of Society 5.0 - Heri Dermawan (International Conference on Elementary Education, 2023)
Scientific literacy is a basic thing that elementary school students must have to enter the era of Society 5.0. Society 5.0 is an example of how data can be used to mobilize and connect everything, including efforts to solve social problems. Scientific literacy is the ability to understand science, communicate science, and solve problems. Efforts to improve scientific literacy. This includes, among others, the application of learning models that are appropriate to the situation and abilities of students so that students can provide direct experience and apply the essence of science. One of them is the application of the scientific multiliteracy model. Learning with this model can connect scientific material with local knowledge. In this case, science based on local wisdom generally applies, but science generally involves concepts and theories. Application of the Scientific Multiliteracy Model Based on Local Wisdom in science learning is expected to have an impact on increasing student literacy, especially elementary school students